2013
DOI: 10.1371/journal.pone.0078312
|View full text |Cite
|
Sign up to set email alerts
|

Cholera Toxin Enhances Vaccine-Induced Protection against Mycobacterium Tuberculosis Challenge in Mice

Abstract: Interleukin (IL)-17 is emerging as an important cytokine in vaccine-induced protection against tuberculosis disease in animal models. Here we show that compared to parenteral delivery, BCG delivered mucosally enhances cytokine production, including interferon gamma and IL-17, in the lungs. Furthermore, we find that cholera toxin, delivered mucosally along with BCG, further enhances IL-17 production by CD4+ T cells over mucosal BCG alone both in the lungs and systemically. This boosting effect of CT is also obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 32 publications
6
21
1
Order By: Relevance
“…Substantial recent evidence demonstrates a pivotal role for Th17 cells and IL-17 in vaccine-mediated immunity against TB [8, 10, 17]. Several mucosally delivered adjuvants such as cholera toxin [26, 27], heat labile enterotoxin [8], Monophosporyl lipid A (MPL) along with chitosan [25], when delivered with Mtb antigens in experimental models have all been shown to induce potent lung Th17 responses and confer Mtb control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Substantial recent evidence demonstrates a pivotal role for Th17 cells and IL-17 in vaccine-mediated immunity against TB [8, 10, 17]. Several mucosally delivered adjuvants such as cholera toxin [26, 27], heat labile enterotoxin [8], Monophosporyl lipid A (MPL) along with chitosan [25], when delivered with Mtb antigens in experimental models have all been shown to induce potent lung Th17 responses and confer Mtb control.…”
Section: Discussionmentioning
confidence: 99%
“…vaccines induce better mucosal immunity and confer superior protection against mucosal infectious diseases, including TB [12-15], when compared to systemic routes of immunization [16]. Importantly, we and others have recently demonstrated that mucosal vaccination of Mtb antigens in Heat Labile enterotoxin (HLT) [8] or cholera toxin [17] induced mucosal Th17 responses, which confer protection upon Mtb challenge. Our mechanistic studies demonstrated that IL-17 induced chemokines localize cytokine-producing T-cells near Mtb -infected macrophages, forming lymphoid follicles within granulomas to mediate Mtb control [11, 18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The attenuated SchuS4 strains induced improved protection over LVS, which was associated with increased IL-17 production in the lungs of challenged mice [40], however intranasal delivery did not improve on intranasal challenge [41]. This is in contrast to results from Mtb vaccine studies in which intranasal delivery confers improved protection over parenteral delivery [7,8], suggesting that the site of T cell induction for optimal responses may differ between pathogens. Provided there is no risk of reversion, thus, live attenuated vaccines represent a valid approach for T cell-inducing vaccines given the potential for induction of an immune response to a broad range of antigens.…”
Section: Live Attenuated Vaccinesmentioning
confidence: 99%
“…In preclinical models, the most largely employed adjuvants to induce mucosal immune responses have been non-toxic derivatives of cholera toxin (CT) and Escherichia coli heat labile enterotoxin (LT). 102,103 Although devoid of their enterotoxicity and capable to efficiently increase both antibody and cellular immune responses, LT-derivatives proved to be toxic to humans after i.n. delivery due to the nerve tissue tropism leading to accumulation in the olfactory nerve and the bulb and inducing transient facial paralysis.…”
Section: Mucosal Adjuvantsmentioning
confidence: 99%